Responsibility Sharing: Towards a Unified Refugee Protection Framework in Africa (African Human Mobility Review, 2021)
In most African countries, refugees are not welcomed with the sense of regional solidarity that surrounded the promulgation of the 1969 OAU Convention Governing the Specific Aspects of Refugee Problems in Africa. Instead, African states have increasingly followed the lead of European states by closing their borders, deporting those who have made it into their territories or restricting them to camps. Even in those countries where refugees are admitted, their treatment does not meet the Convention’s standards and obligations. Despite South Africa having enacted legislation, the Refugees Act, which is hailed as one of the most liberal domestic refugee protection frameworks in Africa, it has regressed in its refugee protection policy.Continued conflict in the Horn of Africa, environmental disasters and struggling economies have resulted in a migratory flow of people to South Africa. This paper will argue that due to the fragmented manner in which African states approach refugee protection, countries such as South Africa, that have liberal and progressive refugee protection frameworks, will continue to experience higher migration flows and thus shoulder a greater responsibility.In response to this migratory pressure, this paper will demonstrate how the South African government has begun to intentionally and unlawfully violate the Refugees Act as well as regional obligations, and will demonstrate how South Africa has adopted policies and practices aimed at hindering, discouraging and restricting access to asylum. This paper will propose that African states should adopt a unified regional approach to refugee protection in order to share the responsibility of refugee protection.